Pelatihan Musik dan Organ Gereja HKBP di Humbang Habinsaran Siborong-Borong - Ance Panggabean (Jurnal Visi Pengabdian Kepada Masyarakat, 2020)
Church Music and Organ Training in Humbang Habinsaran Siborong-borong is one of the goals to help the music team in worship services at the HKBP church. The basic method to be applied in community service is descriptive method. In addition, the approach method used is the skill / skill training method for playing music and organ techniques, so that good and correct music playing techniques are produced. The method of mentoring and teaching playing music and organs both individually and collectively for the music team with the aim of fostering a sense of self-confidence, such as not being awkward, embarrassed, insecure about one's shortcomings, so that music playing activities can be done happily. The process of training for music and church organs is carried out by means of teaching methods both orally and in theory, which are applied through methods of education, training and mentoring. Through both oral teaching methods, theory and practice (demonstration) in this training activity was considered quite successful. Success indicators can be seen and evaluated through small performances carried out jointly by the music team with a song lieder in the last activity carried out in the training.